Insects in the People's Sugarcane Plantations of Nagari Lawang, Matur District, Agam Regency - Yuza, Bunga Zarifa; Safitri, Elza; Zikra, Zikra; Abizar, Abizar (Jurnal Biologi Tropis, 2025)
Insects are the class with the largest number of species and the widest distribution in the Animalia kingdom, this is because insects are organisms that are easily found on the earth's surface. Insects are one of the Arthropod classes that have a body divided into caput, thorax and abdomen. This study aims to determine the types of Insects found in the People's Sugarcane Plantation of Nagari Lawang, Matur District, Agam Regency. This study is a descriptive survey study with direct insect sampling in the field using insect nets with (sweeping) and (hand sorting) techniques. Sampling was carried out using the exploration method at 3 different locations with 2 time periods (morning and afternoon). From the research results, 22 species of insects from 7 orders and 16 families were found, consisting of Aspidimorpha deusta, Lygistopterus perfacetus, Neopyrochroa fermoralis, Epilachna admirabilis, Coelophora inaequalis, Cofana subvirencens, Bothrogonia ferruginea, Gonocerus acuteangulata, Tetrix subulata, Valangan nigricornis, Acrida cinirea, Trilophidia annulata, Tessellana tessellata, Musca domestica, Netelia inedita, Vespa affinis, Ypthima baldus, Forsterinaria quantius, Nyctemera baulus, Hypagyrtis esther, Eurema hecabe, dan Orthetrum Sabina.